Evidence for pre‐symptomatic transmission of coronavirus disease 2019 (COVID‐19) in China. Issue 1 (7th August 2020) - Ren, Xiang; Li, Yu; Yang, Xiaokun; Li, Zhili; Cui, Jinzhao; Zhu, Aiqin; Zhao, Hongting; Yu, Jianxing; Nie, Taoran; Ren, Minrui; Dong, Shuaibing; Cheng, Ying; et al.
Abstract: Background: Between mid‐January and early February, provinces of mainland China outside the epicentre in Hubei province were on high alert for importations and transmission of COVID‐19. Many properties of COVID‐19 infection and transmission were still not yet established. Methods: We collated and analysed data on 449 of the earliest COVID‐19 cases detected outside Hubei province to make inferences about transmission dynamics and severity of infection. We analysed 64 clusters to make inferences on serial interval and potential role of pre‐symptomatic transmission. Results: We estimated an epidemic doubling time of 5.3 days (95% confidence interval (CI): 4.3, 6.7) and a median incubation period of 4.6 days (95% CI: 4.0, 5.2). We estimated a serial interval distribution with mean 5.7 days (95% CI: 4.7, 6.8) and standard deviation 3.5 days, and effective reproductive number was 1.98 (95% CI: 1.68, 2.35). We estimated that 32/80 (40%) of transmission events were likely to have occurred prior to symptoms onset in primary cases. Secondary cases in clusters had less severe illness on average than cluster primary cases. Conclusions: The majority of transmissions are occurring around illness onset in an infected person, and pre‐symptomatic transmission does play a role. Detection of milder infections among the secondary cases may be more reflective of true disease severity.